A comparison of sexual outcomes in primiparous women experiencing vaginal and caesarean births - Khajehei M; Ziyadlou S; Safari Rad; Tabatabaee H; Kashefi F (Wolters Kluwer Medknow Publications, 2009)
Background and Objective: We conducted this study to evaluate and compare postpartum sexual functioning after vaginal and caesarean births. Materials and Methods: This was a cross-sectional study that was carried out in postnatal health care in a hospital. A total of 50 primiprous women who had given birth 6-12 months ago and came to the hospital for postnatal care were asked to join the study. Forty of the women completed the entire questionnaire. Among these women, 20 delivered spontaneously with mediolateral episiotomy and 20 had elective caesarean section. Sexual function was evaluated by a validated, self-created questionnaire. A statistical evaluation was carried out by SPSS v.11. A two-part self-created validated questionnaire for data collection was administered regarding sexual function prior to pregnancy and 6-12 months postpartum. Results: The median time to restart intercourse in the normal vaginal delivery with episiotomy (NVD/epi) group was 40 days and in the caesarean section (C/S) group was 10 days postpartum. The most common problems in the NVD/epi group was decreased libido (80%), sexual dissatisfaction (65%), and vaginal looseness (55%). In the C/S group, the most common problems were vaginal dryness (85%), sexual dissatisfaction (60%), and decreased libido (35%). There were clinically significant differences between the two groups regarding sexual outcomes, but these differences were not statically significant. Conclusion: Postnatal sexual problems were very common after both NVD/epi and C/S. Because sexual problems are so prevalent during the postpartum period, clinicians should draw more attention to the women′s sexual life and try to improve their quality of life after delivery.